Pengaruh Brand Ambassador, Brand Image, Kualitas Produk Terhadap Minat Beli Arascarf (Studi Kasus Konsumen Arascarf di MOG Malang) - Sevty Maya Dewi Fatikhah; Rois Arifin; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine the influence of brand ambassadors, brand image, and product quality on Arascarf buying interest among Arascarf consumers at MOG Malang. The sample in this research is Arascarf consumers at MOG Malang. sampling with a non-probability sampling approach and a purposive sampling strategy, where the sample is chosen after taking into account a number of factors. Seventy respondents made up the study's samples. This study employed quantitative research methods. In this study, SPSS IBM V.28.0 for Windows is used for data analysis. Multiple linear regression analysis is the data testing method that is employed. Validity tests, reliability tests, normality tests, traditional assumption tests, hypothesis tests, and coefficient of determination tests (R2) are all conducted. The factors brand ambassador, brand image, and product quality all had an impact on purchase intention simultaneously or jointly, according to the findings of this study. Purchase intention is partially influenced by brand ambassadors. Purchase intention is partially influenced by brand image. Purchase intention is partially influenced by product quality. Keywords: Brand Ambassador, Brand Image, Product Quality, and Purchase Intention.